Peningkatan Kompetensi Guru Dalam Penyusunan Soal Literasi Berbasis Hots Berbasis Aplikasi Diffit Di SMA Negeri 4 Purwokerto - Laily Nurlina; Wildan Aji Saputra; Eko Sri Israhayu (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The compilation of literacy questions based on higher-order thinking skill or HOTS is one of the important components in improving the quality of learning. This technical guidance activity aims to improve the understanding and skills of SMA Negeri 4 Purwokerto teachers in compiling HOTS based literacy questions by introducing the use of the Diffit for Teachers application. The methods used in this activity include lectures, discussions, practises, and presentations on compiling questions according to subjects. The results of the activity showed an increase in teachers' understanding of the concept of literacy, the application of Bloom's Taxonomy and the use of the Diffit application in making questions. In addition to Diffit for Teachers, teachers were introduced to other supporting digital platforms in compiling questions. This activity has a positive impact on the development of teacher professionalism and is expected to be implemented sustainably in schools.